Fatty Acid Profile and Conjugated Linoleic Acid Content of Milk from Confined Holstein Cows During the Summer and Winter Seasons - Pinelli-Saavedra, Araceli; Martínez-Borraz, Alfonso; Moya-Camarena, Silvia Y.; González-Ríos, Humberto; Hernández, Jesús (IntechOpen, 2012)
None